Caracterização do efeito vasodilatador dos nitratos orgânicos GTN, NTHF, NCOE e BIS-NTHF em artéria e veia isoladas de cordão umbilical humano. - Fernandes, Maria do Carmo de Alustau (2015)
Human umbilical cord vessels (HUCV), often considered biological waste, are good models for evaluation of vasoactive substances. The effect of glyceryl trinitrate (GTN) has been characterized in several animal blood vessels, but this nitrate presents little effect on HUCV. The tetrahydrofurfuryl nitrate (NTHF) and 13-cis-9-octadecanoate acetate nitrate (NCOE) are nitric oxide (NO) donors, whose effect has been characterized in animal vessels. 1,2-bis (tetrahydrofuran-2-yl) ethane-1,2-diildinitrato (BIS-NTHF) is a novel compound (two molecules of NTHF) that has no pharmacological studies. The aim of this study was to implement and standardize the technique involving HUCV, and characterize the effect of these four organic nitrates both in artery (HUA) and vein (HUV) rings isolated from umbilical cord. The standardization of the technique showed that 3g and 3h are, respectively, the ideal voltage and time to experiment with the umbilical vessels, besides the fact that it presents a spontaneous decrease both basal tone as the contractile. The study of nitrates showed that these compounds have relaxed the basal tone of HUCV. All nitrate induced vasorelaxation in both umbilical vessels pre-contracted with serotonin (5-HT), with maximum effects than 90%, and more effectively in relaxing HUA than HUV. In this situation, GTN was the most potent nitrate in causing vasodilation, BIS NTHF presented an intermediate power value, while NCOE and NTHF were less potent in relaxing HUV and HUA, respectively. When HUA rings were pre-contracted with KCl 60 mM, there was an attenuation of vasodilation promoted by nitrates. GTN and the NTHF also showed decreased vasorelaxation in HUV rings contracted with KCl 60 mM, while NCOE and BIS-NTHF have effects similar to the rings pre-contracted with 5 HT. Preincubation of GTN, BIS-NTHF and NTHF attenuated contractions induced by 5-HT in HUA rings. Additionally, GTN and BIS-NTHF also inhibited contraction stimulated by 5-HT in HUV. In contrast, preincubation of NTHF in HUV, and NCOE both in HUV as HUA led to lower inhibition when compared with the other nitrates. GTN, NTHF and BIS-NTHF inhibited the phasic and tonic components of the contraction induced by 5-HT in the absence of extracellular Ca2+. NCOE was more effective to inhibit the tonic contraction. Pre-incubation of 10 μM of ODQ, inhibitor of soluble cyclase guanylyl, attenuated significantly the vasodilator response to GTN, NTHF, NCOE and BIS NTHF was. Preincubation of 10 mM TEA, a blocker of potassium channels, decreased the relaxant response of the four nitrates in HUA, while do not alter the effect in HUV. In view of what has been exposed here, it can be concluded that GTN, NTHF, NCOE and BIS-NTHF cause vasorelaxation of HUCV rings, both in basal tone as contractions induced by 5-HT or KCl. The mechanism of nitrates action in these human vessels involves activation of sCG and channels for potassium; and inhibition of calcium entry, release of stocks of this ion by sarcoplasmic reticulum and ROCK activity.